Crystallographic Engineering Enables Fast Low-Temperature Ion Transport of TiNb2O7 for Cold-Region Lithium-Ion Batteries - Wei, Lihua; Geng, Shenglu; Liu, Hailu; Deng, Liang; Mao, Yiyang; Ning, Yanbin; Wang, Biqiong; Xiong, Yueping; Zhang, Yan; Lou, Shuaifeng (Nano-Micro Letters, 2026)
TiNb2O7 represents an up-and-coming anode material for fast-charging lithium-ion batteries, but its practicalities are severely impeded by slow transfer rates of ionic and electronic especially at the low-temperature conditions. Herein, we introduce crystallographic engineering to enhance structure stability and promote Li+ diffusion kinetics of TiNb2O7 (TNO). The density functional theory computation reveals that Ti4+ is replaced by Sb5+ and Nb5+ in crystal lattices, which can reduce the Li+ diffusion impediment and improve electronic conductivity. Synchrotron radiation X-ray 3D nano-computed tomography and in situ X-ray diffraction measurement confirm the introduction of Sb/Nb alleviates volume expansion during lithiation and delithiation processes, contributing to enhancing structure stability. Extended X-ray absorption fine structure spectra results verify that crystallographic engineering also increases short Nb-O bond length in TNO-Sb/Nb. Accordingly, the TNO-Sb/Nb anode delivers an outstanding capacity retention rate of 89.8% at 10 C after 700 cycles and excellent rate performance (140.4 mAh g−1 at 20 C). Even at −30 °C, TNO-Sb/Nb anode delivers a capacity of 102.6 mAh g−1 with little capacity degeneration for 500 cycles. This work provides guidance for the design of fast-charging batteries at low-temperature condition. Highlights: 1 Sb element is introduced into TiNb2O7 successfully. 2 Such crystallographic engineering can narrow the bandgap and broaden the Li+ transport channel, making TNO-Sb/Nb electrode possess a better low-temperature performance. 3 Such a synergy effect enables TNO-Sb/Nb with large reversible capacity, superior rate performance (140.4 mAh g−1 at 20 C), and a high durability of 500 cycles even at −30 °C, holding brand promises in practical applications.